Las artes plásticas en el desarrollo de la creatividad en niños de 3 a 5 años. - Lapo Chamba, Denisse Carolina; Huertas Rodríguez, Nathaly Marilyn (Machala: Universidad Técnica de Machala, 2024)
The objective of this work is to investigate the plastic arts in the development of creativity in children from 3 to 5 years of initial education, Machala 2024. Through artistic activities, such as painting, modeling and drawing, the aim is to promote individual expression, critical thinking and problem solving at this early stage of child development. The research analyzes how artistic activities contribute to the construction of cognitive, motor and emotional skills, essential for the comprehensive development of children. The work is based on a quantitative methodology, with descriptive scope and nonexperimental design, that is, with non-manipulable variables, observation and interview techniques are used to collect statistical data, The following instruments have been used: a survey with closed questions for the teachers, an observation guide for the teachers and another for the children, their use is to evaluate the application of the plastic arts in the development of creativity to understand how the children are in their autonomy, which were applied to 2 teachers and a sample of 40 children corresponding to the age of 3 to 5 years from the Cleopatra Fernández Castillo Initial Education Center, in the Machala canton. After the application of the instruments, the main result was that, although the plastic arts have a positive influence on the development of children's creativity, there is a lack of application on the part of the teachers with the appropriate use of the plastic arts. Furthermore, due to the lack of training for teachers, they are unable to raise awareness of the importance of teaching strategies, On the other hand, in children it was observed Furthermore, due to the lack of training for teachers, they are unable to raise awareness of the importance of teaching strategies, On the other hand, in children it was observed that they are addressing significant difficulties in their creativity and imagination. The results indicate that frequent contact with the plastic arts stimulates creativity, promoting imagination, the ability to make decisions and self-confidence. It was observed that children who participated in artistic activities demonstrated a greater ability to express their emotions, experiment with new materials and explore different forms of representation. It was concluded that the plastic arts play a fundamental role in the development of creativity in children from 3 to 5 years old, helping them develop key cognitive, social and emotional skills for their integral growth.
El presente trabajo tiene como objetivo investigar las artes plásticas en el desarrollo de la creatividad en niños de 3 a 5 años de educación inicial, Machala 2024, a través de actividades artísticas, como la pintura, el modelado y el dibujo, se busca fomentar la expresión individual, el pensamiento crítico y la resolución de problemas en esta etapa temprana del desarrollo infantil. En la investigación se analiza cómo las actividades artísticas contribuyen a la construcción de habilidades cognitivas, motoras y emocionales, esenciales para el desarrollo integral de los niños. El trabajo se basa en una metodología cuantitativa, con alcance descriptivo y diseño no experimental, es decir con variables no manipulables, para la recopilación de los datos estadísticos se toman las técnicas de observación y entrevista, se ha utilizado los siguientes instrumentos una encuesta con preguntas cerradas para las docentes, una guía de observación para las docentes y otra para los niños, su uso es para poder evaluar la aplicación de las artes plásticas en el desarrollo de la creatividad para comprender como están los niños en su autonomía, mismo que fueron aplicados a 2 docentes y una muestra de 40 niños correspondientes a la edad de 3 a 5 años de la escuela Prof. Cleopatra Fernández Castillo, del cantón Machala. Tras la aplicación de los instrumentos se encontró como resultado principal que, aunque las artes plásticas influyen de manera positiva en el desarrollo de la creatividad de los niños, existe una falta de aplicación por parte de las docentes con en el uso adecuado de las artes plásticas, además por la falta de capacitaciones hacia las docentes no logran concientizar la importancia de las estrategias didácticas, por otro lado, en los niños se observó que están abordando dificultades significativas en su creatividad, imaginación. Los resultados indican que el contacto frecuente con las artes plásticas estimula la creatividad, promoviendo la imaginación, la capacidad de tomar decisiones y la autoconfianza. Se observó que los niños que participaron en actividades artísticas demostraron una mayor capacidad para expresar sus emociones, experimentar con nuevos materiales y explorar diferentes formas de representación. Se concluyo, las artes plásticas juegan un papel fundamental en el desarrollo de la creatividad de los niños de 3 a 5 años, ayudándoles a desarrollar habilidades cognitivas, sociales y emocionales clave para su crecimiento integral.
Keywords: ARTE PLÁSTICA; CREATIVIDAD; DESARROLLO INFANTIL